2023
DOI: 10.1186/s40594-023-00397-9
|View full text |Cite
|
Sign up to set email alerts
|

Learning data science in elementary school mathematics: a comparative curriculum analysis

Abstract: Background Data literacy is increasingly important in today’s data-driven world. Students across many educational systems first formally learn about data in elementary school not as a separate subject but via the mathematics curriculum. This experience can create tensions in the priorities of learning and assessment given the presence of other foundational mathematics content domains such as numbers, algebra, measurement, and geometry. There is a need to study data literacy in comparison to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Learning media play a role in increasing students' interest in learning, which is expected to improve their learning outcomes. This is because learning media can stimulate and direct students' attention, sparking curiosity and enthusiasm for learning (El-Hamamsy et al, 2023;Ow-Yeong et al, 2023). Similar opinions are expressed by Dewi et al (2020) and Setiyani et al (2022), stating that learning media can facilitate students' learning.…”
Section: Introductionmentioning
confidence: 75%
“…Learning media play a role in increasing students' interest in learning, which is expected to improve their learning outcomes. This is because learning media can stimulate and direct students' attention, sparking curiosity and enthusiasm for learning (El-Hamamsy et al, 2023;Ow-Yeong et al, 2023). Similar opinions are expressed by Dewi et al (2020) and Setiyani et al (2022), stating that learning media can facilitate students' learning.…”
Section: Introductionmentioning
confidence: 75%
“…• Online and Blended Learning: Leveraging online platforms for teaching and learning, allowing for more personalized and accessible STEM education (Owston et al, 2020). • Data Analytics: Using data analytics tools in the curriculum to teach students how to interpret and use data, an essential skill in modern STEM professions (Ow-Yeong et al, 2023).…”
Section: The Role Of Technology In Stem Educationmentioning
confidence: 99%
“…• Improved Academic Performance: Studies have shown that students engaged in comprehensive STEM education often perform better not only in science and mathematics but also in other academic areas, due to the interdisciplinary approach and emphasis on analytical skills (Eroğlu & Bektaş, 2022;Nağaç & Kalayci, 2021;Taşdemir, 2022). • Development of Technical Skills: STEM education equips students with specific technical skills, such as programming, data analysis, and scientific experimentation, which are increasingly important in the digital age (Baterna et al, 2020;Ow-Yeong et al, 2023). • Fostering Creativity and Innovation: By integrating technology and engineering principles with science and mathematics, STEM education encourages creative solutions and innovation, skills highly valued in various fields (Eroğlu & Bektaş, 2022;Sonthong et al, 2023).…”
Section: Effects On Student Performance and Skill Development Stem Ed...mentioning
confidence: 99%
“…We used both Singapore (N = 5986) and Korea (N = 3893) datasets for Grade 4 science. These two Asian countries have high-performing educational systems, exhibit seemingly similar cultural values, and are commonly studied in a comparative manner (Kim, 2019;Ow-Yeong et al, 2023;Sandoval-Hernández & Białowolski, 2016).…”
Section: Datamentioning
confidence: 99%